PERAN KOMUNIKASI KELOMPOK TANI PADI SAWAH DALAM PENINGKATAN KAPASITAS ANGGOTA DI KELURAHAN BARGUGA KECAMATAN BARUGA KOTA KENDARI - Aron, Muhammad; Wunawarsih, Ima Astuty; Lasinta, Megafirmawanti (Universitas Halu Oleo, 2024)
The objective of this study is to examine the role of farmer group communication on the capacity of members of the paddy rice group in Baruga Village, Baruga District, Kendari City. The population under investigation consisted of all members of the paddy rice farmer group, which numbered 16 groups with a total membership of 160 farmers. The research sample was determined using the Slovin formula, with a confidence level of 90% or 10% of the total population sampled. This resulted in a sample size of 54 respondents. Data collection techniques employed survey methods, interviews, and documentation using research instruments in the form of questionnaires. The research employed a quantitative approach, utilizing quantitative descriptive analysis through the application of the class interval formula and the Spearman rank correlation formula, with the assistance of the SPSS software version 26. The findings indicated that the communication role within the rice paddy farmer group in Baruga Village, Baruga District, Kendari City, with respect to the information aspect, was categorized as